Use of psylocibin as a psychotherapeutic tool in the treatment of depression: a review - Silva, Joveni Ribeiro da (2021)
Psilocybin is a substance with psychoactive effects that is present in mushrooms of the psilocybe genus. According to Griffiths et al. (2011) the use of psilocybin is perceived as a spiritual and mystical experience, positive and pleasant. The effect of psilocybin is influenced by mental state, experiences prior to use, personality dimension and environmental conditions. The objective of this work was to carry out a literature review on the use of psilocybin aiming at its applicability as a therapeutic tool in the promotion of mental health. To search for articles, searches were performed from March 1, 2021 to July 30, 2021, in Google Scholar and pubmed tools using the keywords: ‘psilocybin’ ‘psilocybin’ ‘depression’. The information contained in this work was obtained through a literature review, with a theoretical approach, carried out in articles published with databases indexed in Scientific Electronic Library Online (SciELO) and Medline (Medical Literature Analysis and Retrievel System Online). This paper provides a review of the existing literature on psilocybin, firstly addressing depression and the difficulties in its treatment, and subsequently addressing psychedelic drugs and psilocybe mushrooms, a little about psilocybin, its mechanism of action and its applicability for psychotherapeutic purposes and the use of psilocybin in Brazil. Therefore, this work results in making more known the benefits of psilocybin aimed at the treatment of Major Depressive Disorder (MDD). In this way, the aim is to contribute to society, through this bibliographic research, in order to allow the use of psilocybin in the treatment of depression to become better known by the scientific community and its use to be further explored for pharmacological purposes related to the treatment of this and other mood disorders.